Clinical progression of cats with early‐stage chronic kidney disease fed diets with varying protein and phosphorus contents and calcium to phosphorus ratios. (21st September 2021) - Schauf, Sofia; Coltherd, Jennifer C.; Atwal, Jujhar; Gilham, Matthew; Carvell‐Miller, Laura J.; Renfrew, Helen; Elliott, Jonathan; Elliott, Denise; Bijsmans, Esther S.; Biourge, Vincent C.; Watson, Phillip; Bakke, Anne Marie
Abstract: Background: Dietary protein and phosphorus (P) restriction is the mainstay for nutritional management of chronic kidney disease (CKD). However, adequate restriction levels for cats with early CKD remain unclear. Objectives: To investigate responses in cats with early CKD to varying dietary protein, P, and calcium (Ca) : P ratio. Animals: Nineteen research colony cats with International Renal Interest Society stages 1‐2 CKD. Methods: In an opportunistic longitudinal case study, cats were fed a low protein (59 g/Mcal), low P (0.84 g/Mcal) dry diet (LP‐LP; Ca : P = 1.9) for 18 months and later transitioned onto a moderate protein (76‐98 g/Mcal), moderate P (1.4‐1.6 g/Mcal) dry‐wet diet regimen (MP‐MP; Ca : P = 1.4‐1.6) for 22 months. Fold‐changes in serum creatinine, total Ca (tCa) and P (primary outcomes) and fibroblast growth factor 23 (FGF23) were assessed by linear‐mixed models. Results: While feeding LP‐LP, mean serum creatinine decreased (0.87‐fold, 95% confidence interval [CI] 0.81, 0.93, P < .001) to within reference range after 6 months, while increases in total Ca (tCa; 1.16‐fold, 95% CI 1.11, 1.22, P < .001) and FGF23 (2.72‐fold, 95% CI 1.72, 4.31, P < .001), but not in P (1.03‐fold, 95% CI 0.945, 1.124, P = .94), were observed after 17 months. On MP‐MP, mean creatinine, tCa and P remained within reference ranges and did not significantly change ( P = .11, P = .98, and P = 1, respectively), while FGF23 significantly decreased (0.58‐fold, 95% CI 0.36, 0.95, P = .02) after 22 months. Conclusions and Clinical Importance: Cats with early CKD developed hypercalcemia after long‐term feeding of a highly P‐restricted diet. Increasing dietary P and reducing Ca : P ratio maintained renal markers, while improving Ca‐P balance. Cats with early CKD could benefit from moderately protein‐ and P‐restricted diets.